High-purity, stable-phase and anti-sintering zirconia-based coating and preparation method thereof

Through atmospheric plasma spraying technology and high-temperature aging heat treatment, a high-purity, phase-stable, and anti-sintered zirconia-based coating was prepared, solving the problem of failure of YSZ coating at high temperatures, achieving higher phase stability and anti-sintering Characteristics extend the service life of the coating.

CN119121112APending Publication Date: 2024-12-13SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411092911.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing YSZ coating is prone to failure due to t′ phase decomposition and grain sintering in high temperature environments, resulting in a decrease in its high temperature durability. The phase stability and grain growth behavior are affected by impurities, making it difficult to prepare higher temperature bearing and long life. coating.

Method used

The high-purity, phase-stable, and anti-sintered zirconia-based coating was prepared by atmospheric plasma spraying technology, controlling the low melting point element content of Si, Al and Fe, and optimizing the phase composition and grain structure of the coating through high-temperature aging heat treatment of 1400°C. , ensure the stability and sintering resistance of the t′ phase.

Benefits of technology

The phase stability and anti-sintering properties of the coating are significantly improved, and the service life of the coating is extended, ensuring excellent performance at higher temperatures and avoiding early failure and sintering cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121112A_ABST
    Figure CN119121112A_ABST
Patent Text Reader

Abstract

The invention relates to a high-purity, stable-phase and anti-sintering zirconia-based coating and a preparation method thereof. The preparation method of the high-purity, stable-phase and anti-sintering zirconia-based coating comprises the following steps: depositing coating raw material powder on the surface of a base material by adopting an atmospheric plasma spraying technology to obtain the high-purity, stable-phase and anti-sintering zirconia-based coating, the coating raw material powder comprises the following chemical components in percentage by mass: greater than or equal to 90 percent of ZrO2, 0 to 0.05 percent of Al2O3, 0 to 0.04 percent of TiO2, 0 to 0.05 percent of SiO2, 0 to 0.03 percent of Fe2O3 and the balance of Y2O3 and HfO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature thermal protective coatings, and specifically relates to a high-purity, phase-stable, sintering-resistant zirconium oxide-based coating and a preparation method thereof. Background Art

[0002] The continuous increase in the gas inlet temperature of aircraft engine turbines and gas turbines (~2000℃ / ~1600℃) makes the long-term stable service of engine components under high temperature conditions a key issue. Thermal barrier coatings are an inevitable choice for achieving leapfrog development of aircraft / gas turbines. Yttria partially stabilized zirconia (YSZ) thermal barrier coatings with excellent properties such as high melting point, low thermal conductivity, high thermal expansion coefficient and fracture toughness have been widely used in aircraft engines and industrial gas turbines to improve their efficiency conversion rate and high temperature durability of hot end components.

[0003] Atmospheric Plasma Spray (APS) YSZ coating is mainly composed of non-transformable tetragonal phase (t'). As a ferroelastic phase, the domain transformation toughening mechanism of t' phase in high temperature section and the martensitic transformation toughening effect of tetragonal phase (t) to monoclinic phase (m) in low temperature section are the key to the long service life of the coating. With the extension of service time, the decomposition of t' phase, the massive generation of m phase, grain growth and sintering shrinkage in the coating are the main reasons for the failure of YSZ ceramic layer.

[0004] Conventional coatings are affected by impurity elements. Under ultra-high temperature flow conditions, the ceramic layer material prematurely changes phase and becomes unstable and over-sintered, which greatly reduces its high temperature durability. In addition, the coating phase stability, grain growth behavior and impurity element influence are coupled. Therefore, the preparation of higher temperature-resistant and long-life YSZ coatings will provide reliable technical support for the development of high-performance aircraft / engines. Summary of the invention

[0005] In view of the above technical problems, the object of the present invention is to provide a high-purity, phase-stable, sintering-resistant zirconia-based coating and a preparation method thereof. The ceramic coating has excellent phase stability and sintering resistance and can significantly optimize the service characteristics of the coating.

[0006] In a first aspect, the present invention provides a method for preparing a high-purity, phase-stable, sinter-resistant zirconia-based coating, the preparation method comprising the following steps: using atmospheric plasma spraying technology to deposit a coating raw material powder on a substrate surface to obtain the high-purity, phase-stable, sinter-resistant zirconia-based coating; The chemical composition of the coating raw material powder includes, by mass percentage, ZrO2: ≥90%, Al2O3: 0-0.05%, TiO2: 0-0.04%, SiO2: 0-0.05%, Fe2O3: 0-0.03%, and the remainder is Y2O3 and HfO2.

[0007] Preferably, the phase composition of the coating raw material powder includes t' phase, t phase, c phase and m phase; preferably, the volume percentage of t' phase in the coating raw material powder is not less than 40%, the volume percentage of t phase is 10-20%, the volume percentage of c phase is 10-15%, and the rest is m phase.

[0008] Preferably, the particle size distribution of the coating raw material powder is 12.5-45.0 μm.

[0009] Preferably, the process parameters of the atmospheric plasma spraying technology include: plasma gas Ar flow rate of 30-36slpm, plasma gas H2 flow rate of 7-9slpm, carrier gas Ar flow rate of 3.0-3.5slpm, spraying distance of 70-130mm, powder feeding rate of 25-40g / min, and power of 39-43kW.

[0010] Preferably, the element composition of the high-purity, phase-stable, sintering-resistant zirconia-based coating includes, by mass percentage, Zr: 55-65%, Y: 3.47-6%, Hf: 1.4-1.6%, Si: 0-0.10%, Fe: 0-0.15%, Ti: 0-0.05%, Al: 0-0.10%, O: 30-35%; Preferably, Zr: 55-65%, Y: 4-6%, Hf: 1.4-1.6%, Si: 0-0.10%, Fe: 0-0.15%, Ti: 0-0.05%, Al: 0-0.10%, O: 30-35%.

[0011] Preferably, the phase composition of the high-purity, phase-stable, sintering-resistant zirconia-based coating includes t′ phase, t phase and c phase, without m phase; preferably, the volume percentage of t′ phase is 60-65%, the volume percentage of c phase is 10-15%, and the rest is t phase.

[0012] Preferably, after the high-purity, phase-stable, sintering-resistant zirconia-based coating is heat treated at 1400°C for 0-300h: the volume percentage of the t′ phase in the coating is not less than 20%, the volume percentage of the m phase is less than 5%, and the rest is t phase and c phase; the average grain size is less than 2μm, preferably 1.50-1.60μm.

[0013] Preferably, the grain size of the high-purity, phase-stable, sintering-resistant zirconia-based coating is calculated by the Scherrer formula to be 0.08±0.01 μm, which is in a submicron state; The high-purity, phase-stable, sintering-resistant zirconia-based coating has a grain growth activation energy of 223.05±14.96 kJ / mol.

[0014] In a second aspect, the present invention provides a high-purity, phase-stable, sintering-resistant zirconia-based coating obtained according to the above preparation method.

[0015] Beneficial Effects The upper limit temperature of stable service of conventional YSZ ceramic coating is 1200°C. At higher temperatures, premature decomposition of t′ phase and rapid sintering and cracking of grains will occur. In the present invention, high-purity YSZ coating is prepared by atmospheric plasma spraying, and the mass percentage of two low-melting-point elements Si and Al in the sprayed coating is controlled at a lower level. By high-temperature aging heat treatment of the ceramic coating at 1400°C, it can be seen that the coating exhibits more excellent phase stability and anti-sintering properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD diagram of the high-purity, phase-stable, sintering-resistant zirconia-based coating prepared in Example 1 of the present invention; Figure 2 XRD diagram and representative grain morphology diagram of the high-purity, phase-stable, sintering-resistant zirconia-based coating prepared in Example 1 of the present invention after heat treatment for 50h@1400°C; Figure 3 XRD diagram and representative grain morphology diagram of the high-purity, phase-stable, sintering-resistant zirconia-based coating prepared in Example 2 after heat treatment for 150h@1400°C; Figure 4 XRD diagram and representative grain morphology diagram of the high-purity, phase-stable, sintering-resistant zirconia-based coating prepared in Example 3 after heat treatment for 300h@1400℃; Figure 5 is the XRD pattern of the coating prepared in Comparative Example 1; Figure 6 XRD diagram and representative grain morphology of the coating prepared in Comparative Example 1 after heat treatment at 1400°C for 40h; Figure 7 XRD pattern and representative grain morphology of the coating prepared in Comparative Example 2 after heat treatment for 160h@1400℃; Figure 8 XRD pattern and representative grain morphology of the coating prepared in Comparative Example 3 after heat treatment at 1400°C for 320h. DETAILED DESCRIPTION

[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0018] The following is an exemplary description of the preparation method of the high-purity, phase-stable, sinter-resistant zirconia-based coating provided by the present invention, wherein the preparation method comprises the following steps: using atmospheric plasma spraying technology to deposit the coating raw material powder on the surface of a substrate such as stainless steel to obtain the high-purity, phase-stable, sinter-resistant zirconia-based coating.

[0019] In some embodiments, the chemical composition of the coating raw material powder may include, by mass percentage, ZrO2: ≥90%, Al2O3: 0-0.05%, TiO2: 0-0.04%, SiO2: 0-0.05%, Fe2O3: 0-0.03%, and the remainder is Y2O3 and HfO2, wherein HfO2 is a symbiotic substance of ZrO2.

[0020] In some embodiments, the phase composition of the coating raw material powder includes t' phase, t phase, c phase and m phase; preferably, the volume percentage of t' phase in the coating raw material powder is not less than 40%, the volume percentage of t phase is 10-20%, the volume percentage of c phase is 10-15%, and the rest is m phase.

[0021] In some embodiments, the particle size distribution of the coating raw material powder may be 12.5-45.0 μm.

[0022] In some embodiments, the process parameters of the atmospheric plasma spraying technology may include: plasma gas Ar flow rate of 30-36slpm, plasma gas H2 flow rate of 7-9slpm, carrier gas Ar flow rate of 3.0-3.5slpm, spraying distance of 70-130mm, powder feeding rate of 25-40g / min, and power of 39-43kW.

[0023] The high-purity, phase-stable, sinter-resistant zirconia-based coating is a YSZ ceramic coating. In some embodiments, the elemental composition of the high-purity, phase-stable, sinter-resistant zirconia-based coating may include: in mass percentage, Zr: 55-65%, Y: 3.47-6%, Hf: 1.4-1.6%, Si: 0-0.10%, Fe: 0-0.15%, Ti: 0-0.05%, Al: 0-0.10%, O: 30-35%; preferably, Zr: 55-65%, Y: 4-6%, Hf: 1.4-1.6%, Si: 0-0.10%, Fe: 0-0.15%, Ti: 0-0.05%, Al: 0-0.10%, O: 30-35%.

[0024] The phase change and grain sintering growth behavior of the coating under high temperature and other working conditions are significantly affected by the internal elements. Considering the volatilization loss of elements in the high-temperature flame flow during plasma spraying, the present invention uses a coating raw material powder with a specific chemical composition to finally prepare a high-purity, phase-stable, sinter-resistant zirconia-based coating that meets the requirements of special elements.

[0025] Generally speaking, it is believed that coatings with lower impurity element content levels will have higher high-temperature phase stability and anti-sintering properties. Different impurity elements in the coating will also show different effects on its high-temperature service behavior, specifically: (1) During the high-temperature heat treatment of the coating sample (~1400°C), the low-melting-point elements Si and Al will diffuse to the grain boundary region to form corresponding molten salts and produce a viscous flow glass phase. The production of the glass phase will accelerate the mass transfer and diffusion rate between different grains, thereby causing liquid phase sintering to further promote the growth of grains and the alternation of phases. Therefore, the contents of both Si and Al in the present invention are controlled at a relatively low level, ensuring that the coating has higher phase stability and anti-sintering properties than conventional coatings. (2)Fe 3+ In the 8YSZ lattice, there are more substitutional defects. However, during the high-temperature sintering process, the migration rate of the interstitial defect elements is higher than the migration rate of the vacancies generated by substitution, and Fe 3+ Radius smaller than Zr 4+ , Y 3+ , O 2- radius, so the iron ions are more inclined to transition from substitution positions to interstitial positions, and the cation vacancies generated by the transition are the main ions of the coating (Zr 4+ , Y 3+ ) provides a location for diffusion and migration, thereby accelerating the diffusion rate of ions; from the perspective of chemical bond strength, the introduction of elements such as Fe causes the original Zr-O bond to be replaced by Fe-O, reducing the overall interatomic bonding force of the system, and also increasing the element diffusion rate, thereby further promoting mass transfer efficiency, accelerating grain growth and sintering degree, so the Fe content is controlled at a relatively low level in the present invention, which can ensure that the coating has good anti-sintering performance; (3) Ti 4+ Doping in the YSZ lattice will increase the tetragonality (c / a) of the t′ phase lattice, and the relaxation time of the t′ phase in a high-temperature service environment is the key to the durability of the coating. The present invention can promote the improvement of the service life of the coating by introducing a certain content of Ti element.

[0026] In some embodiments, the physical phase composition of the high-purity, phase-stable, sintering-resistant zirconia-based sprayed coating may include a non-phase-transformable tetragonal phase (t′), a tetragonal phase (t) and a cubic phase (c), and no monoclinic phase (m); preferably, the volume percentage of the t′ phase is 60-65%, the volume percentage of the c phase is 10-15%, and the rest is the t phase.

[0027] The large amount of t' phase in the coating powder is one of the keys to the t' phase as the main crystalline phase in the sprayed coating. At the same time, the powder melts in the high-temperature plasma flame, and the rapid solidification of the molten droplets on the substrate makes the stabilizer Y 3+ The diffusion of elements is hindered and the expected t' phase is generated. In addition, the powder melts in the high-temperature plasma flame flow, and the inherent monoclinic phase can be transformed into the tetragonal phase and the cubic phase by controlling the residence time of the powder in the flame flow, thereby ensuring that the sprayed coating does not contain the monoclinic phase. The powder particle size distribution range is concentrated (12.5-45.0μm), so that it can show good melting-deposition characteristics in the plasma flame flow.

[0028] Specifically, the phase change process of the YSZ coating provided by the present invention in a high temperature environment is mainly divided into two stages: (1) The first stage is the t′ phase destabilization and decomposition stage. The heat treatment process is the process of the stabilizer Y in the coating. 3+ Provide a certain diffusion power, so the t′ phase in the sprayed coating undergoes spinodal decomposition to generate yttrium-poor t phase and yttrium-rich c phase; (2) The second stage is the surge of m phase. Under long-term heat treatment conditions, the content of tetragonal and cubic phases in the coating continues to rise. In the subsequent cooling process, a large amount of tetragonal zirconia undergoes martensitic transformation, resulting in a surge of monoclinic zirconia. As a ferroelastic phase, the t′ phase can effectively extend the service life of the coating by improving the fracture toughness of the coating through its ferroelastic domain reversal toughening mechanism in a high-temperature environment. The toughening effect introduced by the martensitic transformation of the t phase to the m phase further extends the service life of the coating under low-temperature conditions. However, the transformation of the t phase to the m phase will be accompanied by a 3% volume increase, and the generation of a large amount of monoclinic phase will cause the coating to crack. Therefore, extending the stable service time of the t′ phase and slowing down the generation of the m phase are the key to improving the service life of the coating.

[0029] Based on this, requirements are put forward for the phase composition of the sprayed coating. On the one hand, the APS sprayed coating of the present invention is mainly t'. The high-temperature fracture toughness strengthening mechanism provided by this phase is the key to the coating's ability to withstand flame scouring and particle erosion during service. Therefore, the t' phase content in the sprayed state is required to be not less than 60%; on the other hand, the c content in the sprayed coating should be increased to a certain level. Since the t' phase will undergo amplitude modulation decomposition to generate t phase and c phase during high-temperature service, increasing the c content in the sprayed coating can not only inhibit the decomposition of t', but also based on the competition mechanism between the c phase and the t' phase during the high-temperature phase change process, the presence of the c phase further slows down the decomposition rate of the t' phase, thereby extending the service time of the t' phase. However, since the c phase is a fully stable phase, too much c phase in the coating will reduce its fracture toughness and increase the Young's modulus, which will cause premature failure of the coating during thermal service. Therefore, it is required to control the c phase in the sprayed coating to 10-15%. In addition, in order to provide a certain content margin for the c phase, the upper limit of the t' phase content in the sprayed coating needs to be controlled to 65%. In summary, the control of the phase content in the sprayed coating should meet the following requirements: t′ phase 60-65%, c phase 10-15%, no m phase, and the rest is t phase formed during the spraying process.

[0030] In some embodiments, the high-purity, phase-stable, sinter-resistant zirconia-based coating is heat-treated at 0-300h@1400℃ (e.g., 300h@1400℃): the volume percentage of the t' phase in the coating is not less than 20%, the volume percentage of the m phase is less than 5%, and the rest is the t phase and the c phase; the average grain size is less than 2μm, preferably 1.50-1.60μm; there is no obvious grain cracking in the coating, and the coating exhibits better high-temperature phase stability and sintering resistance. According to industry recognition, a monoclinic phase content of less than 5% in the coating will not cause the coating to fail, and at least 20% of the t' phase also represents the long-term service, reliability and stability of the coating in high-temperature environments such as 1400℃.

[0031] In some embodiments, the grain size of the high-purity, phase-stable, sintering-resistant zirconia-based (sprayed) coating is 0.08±0.01 μm calculated by the Scherrer formula, which is submicron.

[0032] During the high-temperature sintering process, the movement of grain boundaries in the coating promotes grain growth, and the grains develop towards an equiaxed crystal morphology by prolonging the heat treatment time. In addition, high-temperature heat treatment intensifies element diffusion, among which the stabilizer element yttrium undergoes directional diffusion and element segregation occurs. The yttrium-rich region in the grain promotes the nucleation of the c phase, and the yttrium-poor region promotes the nucleation of the t phase. After the phase transformation occurs, the internal thermal stress of each phase is uneven, so that different parts of the same grain will have different stress levels. The heat treatment continues, and the grains grow steadily. Since the phase transformation is coupled with the grain growth behavior, when the grain size increases beyond the critical value, the martensitic phase transformation occurs during the cooling process. The stress introduced immediately induces phenomena such as grain boundary widening and grain cracking. At the same time, in different crystallization directions of the grains, due to the anisotropy of the crystal, the grain boundary stress introduced by the difference in linear expansion coefficients of the grain boundaries on both sides of the grain boundary will cause cracks to germinate and proliferate along the grain boundary. Considering that the internal grain growth of APS spray coating is affected by its position distribution (cracks, pores), the grain sizes in different parts of the coating are different, so the average grain size of the coating represents the overall development trend of the coating heat treatment. Among them, it is determined that grains smaller than 2μm have not undergone the transformation of the monoclinic martensitic phase, and the coating with an overall average grain size of 1.5-1.6μm after heat treatment will maintain a low m-phase content.

[0033] The grain growth difficulty of the ceramic coating provided by the present invention is quantitatively analyzed. In some embodiments, the grain growth activation energy of the high-purity, phase-stable, sinter-resistant zirconia-based coating can be 223.05±14.96 kJ / mol. It is significantly higher than the grain growth activation energy of conventional coatings (198.41±3.30 kJ / mol). Therefore, compared with conventional YSZ coatings, the coating provided by the present invention has a higher grain growth activation energy. Under the same heat treatment conditions, more energy is required for grain growth, and grain growth is slower, showing better anti-sintering properties.

[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0035] Example 1

[0036] The method for preparing the high-purity, phase-stable, sintering-resistant ceramic coating provided in this embodiment comprises the following steps: (1) Stainless steel is used as the substrate, and then ultrasonically cleaned, degreased and dried; (2) A high-purity, phase-stable, sintering-resistant zirconia-based coating (YSZ ceramic coating) was prepared on the surface of a stainless steel substrate using an atmospheric plasma spraying process. in: The content of each element in the coating raw material powder is: calculated by mass percentage of each element oxide, ZrO2: 90.50%, Y2O3: 7.43%, HfO2: 1.92%, Al2O3: 0.05%, TiO2: 0.04%, SiO2: 0.05%, Fe2O3: 0.01%; The spraying parameters are: plasma gas Ar flow rate is 30-36slpm, plasma gas H2 flow rate is 7-9slpm, carrier gas Ar flow rate is 3.0-3.5slpm, spraying distance is 70-130mm, powder feeding rate is 25-40g / min, power is 39-43kW; The element composition of the sprayed coating includes, by mass percentage, Zr: 62.98wt.%, Y: 3.47wt.%, Hf: 1.54wt.%, Si: 0.01wt.%, Fe: 0.14wt.%, Ti: 0wt.%, Al: 0.01wt.%, O: 31.85wt.%;

[0037] Figure 1 This is the XRD diagram of the high-purity, phase-stable, sintering-resistant zirconia-based coating prepared in Example 1 of the present invention. It can be seen from the figure that the phase composition of the sprayed ceramic coating includes t' phase, t phase and c phase, and the volume percentage of each phase is 60.17%, 26.49% and 13.34% respectively.

[0038] After the above coating was subjected to 50h@1400℃, the coating phase was qualitatively and quantitatively analyzed, and multiple (>5) grain morphology images of the sample at different positions and uniform magnifications (5K-10K) were taken to calculate the average grain size (calculated based on the equivalent circular diameter of the grain). Figure 2 The XRD diagram and representative grain morphology diagram of the high-purity, phase-stable, sintering-resistant zirconia-based coating prepared in Example 1 of the present invention after 50h@1400℃ heat treatment. Characterization shows that the phase distribution and corresponding volume percentage of the coating prepared in Example 1 after 50h@1400℃ heat treatment are: m phase 1.11%, t' phase 33.58%, t phase 43.29% and c phase 22.02%, among which the m phase content is very small and the t' phase begins to decompose; the average grain size of the coating prepared in Example 1 after 50h@1400℃ heat treatment is 0.95±0.16μm, and most of the grains are submicron.

[0039] Example 2

[0040] The preparation method of the high-purity, phase-stable, sintering-resistant ceramic coating provided in this Example 2 refers to that in Example 1, the main difference is that the coating is heat-treated for 150h@1400°C.

[0041] Figure 3 The XRD diagram and representative grain morphology diagram of the high-purity, phase-stable, sintering-resistant zirconia-based coating prepared in Example 2 after 150h@1400℃ heat treatment. Characterization shows that the phase distribution and corresponding volume percentage of the coating prepared in Example 2 after 150h@1400℃ heat treatment are: m phase 2.79%, t' phase 29.43%, t phase 43.76% and c phase 24.03%, among which the m phase content is less and the t' phase decomposition is reduced; the average grain size of the coating prepared in Example 2 after 150h@1400℃ heat treatment is 1.27±0.13μm, and the grains grow up by sintering.

[0042] Example 3

[0043] The preparation method of the high-purity, phase-stable, sintering-resistant ceramic coating provided in this Example 3 refers to that in Example 1, the main difference is that the coating is heat-treated for 300h@1400°C.

[0044] Figure 4 The XRD diagram and representative grain morphology diagram of the high-purity, phase-stable, sinter-resistant zirconia-based coating prepared in Example 3 after 300h@1400℃ heat treatment. Characterization shows that the phase distribution and corresponding volume percentage of the coating prepared in Example 3 after 300h@1400℃ heat treatment are: m phase 3.15%, t′ phase 21.20%, t phase 48.95% and c phase 26.70%, wherein the m phase content is still relatively small; the average grain size of the coating prepared in Example 3 after 300h@1400℃ heat treatment is 1.54±0.19μm, the grains grow significantly, but no grain cracking and grain boundary cracks are observed, the grain size is less than 2μm, and the sintering resistance is good.

[0045] Comparative Example 1

[0046] The preparation method of the coating provided in this comparative example 1 refers to that in Example 1, the main difference is that the content of each element included in the raw material powder is: calculated as the mass percentage of each element oxide, ZrO2: 90.63%, Y2O3: 7.04%, HfO2: 1.72%, Al2O3: 0.05%, TiO2: 0.13%, SiO2: 0.33%, Fe2O3: 0.03%. in: The element composition of the sprayed coating includes, by mass percentage, Zr: 60.15wt.%, Y: 3.42wt.%, Hf: 1.17wt.%, Si: 0.36wt.%, Fe: 0.05wt.%, Ti: 0.08wt.%, Al: 0.10wt.%, O: 34.59wt.%;

[0047] Figure 5 The XRD diagram of the coating prepared in Comparative Example 1. The test shows that the phase composition of the sprayed ceramic coating includes t', t and c phases, and the volume percentages of the phases are 85.10%, 11.61% and 3.29% respectively, and there is no m phase. The grain size of the sprayed coating is calculated by the Scherrer formula to be 0.06±0.01μm.

[0048] After the above coating was heat treated at 1400° C. for 40 h, the coating phase and grain morphology were characterized in the same manner as in Example 1. Figure 6 The XRD diagram and representative grain morphology diagram of the coating prepared in Comparative Example 1 after heat treatment at 40h@1400℃. Characterization shows that the phase distribution and corresponding volume percentage of the coating prepared in Comparative Example 1 after heat treatment at 40h@1400℃ are: m phase 1.44%, t' phase 16.79%, t phase 57.17% and c phase 24.58%, among which the m phase content is relatively small, but the t' phase is severely decomposed and its content is significantly reduced; the average grain size of the coating prepared in Comparative Example 1 after heat treatment at 40h@1400℃ is 1.20±0.06μm, and the grains grow significantly.

[0049] Comparative Example 2

[0050] The preparation method of the coating provided in this comparative example 2 refers to that of comparative example 1, with the main difference being that the coating is heat treated for 160h@1400°C.

[0051] Figure 7 The XRD diagram and representative grain morphology diagram of the coating prepared in Comparative Example 2 and heat treated for 160h@1400℃. It was characterized that the phase distribution and corresponding volume percentage of the coating prepared in Comparative Example 2 and heat treated for 160h@1400℃ were: m-phase 28.69%, t′ phase 11.75%, t-phase 22.11% and c-phase 37.45%. The t′ phase content continued to decrease, and the t-phase content also decreased. This was mainly due to the large amount of martensitic phase transformation during the cooling process, which caused the t-phase to transform into the m-phase, thereby causing a surge in harmful phases. The m-phase content in the sample of Comparative Example 2 is much greater than the m-phase content in the sample of Example 3, and the phase stability of Comparative Example 2 is significantly reduced.

[0052] It was characterized that the average grain size of the coating prepared in Comparative Example 2 and heat treated at 1400°C for 160h was 1.77±0.20 μm, which was larger than the average grain size of Example 3. In addition, more grain boundary widening and grain cracking phenomena were observed in this comparative example.

[0053] Comparative Example 3

[0054] The preparation method of the coating provided in this comparative example 3 refers to that of comparative example 1, with the main difference being that the coating is heat treated for 320h@1400°C.

[0055] Figure 8 The XRD diagram and representative grain morphology diagram of the coating prepared in Comparative Example 3 after 320h@1400℃ heat treatment. Characterization shows that the phase distribution and corresponding volume percentage of the coating prepared in Comparative Example 3 after 320h@1400℃ heat treatment are: m-phase 37.70%, t'phase 8.35%, t-phase 10.26% and c-phase 43.69%. The content of m-phase and c-phase in the sample of Comparative Example 3 is almost the same, and the contents of the two tetragonal phases are both at a low level.

[0056] It was characterized that the average grain size of the coating prepared in Comparative Example 3 after heat treatment for 320h@1400℃ was 1.96±0.36μm, the number of abnormally grown grains increased, and cracks and transgranular cracks appeared on the surface of large grains. The phase stability and anti-sintering properties of the sample in Comparative Example 3 were significantly reduced.

[0057] Table 1 below summarizes the volume percentage content and average grain size data of each phase in the above-mentioned embodiments and comparative examples:

[0058] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a high-purity, phase-stable, sintering-resistant zirconium oxide-based coating, characterized in that: The preparation method comprises the following steps: using atmospheric plasma spraying technology to deposit coating raw material powder on the surface of the substrate to obtain the high-purity, phase-stable, sintering-resistant zirconia-based coating; The chemical composition of the coating raw material powder includes, by mass percentage, ZrO2: ≥90%, Al2O3: 0-0.05%, TiO2: 0-0.04%, SiO2: 0-0.05%, Fe2O3: 0-0.03%, and the remainder is Y2O3 and HfO2.

2. The preparation method according to claim 1, characterized in that: The phase composition of the coating raw material powder includes t' phase, t phase, c phase and m phase; preferably, the volume percentage of t' phase in the coating raw material powder is not less than 40%, the volume percentage of t phase is 10-20%, the volume percentage of c phase is 10-15%, and the rest is m phase.

3. The preparation method according to claim 1 or 2, characterized in that: The particle size distribution of the coating raw material powder is 12.5-45.0 μm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The process parameters of the atmospheric plasma spraying technology include: plasma gas Ar flow rate of 30-36slpm, plasma gas H2 flow rate of 7-9slpm, carrier gas Ar flow rate of 3.0-3.5slpm, spraying distance of 70-130mm, powder feeding rate of 25-40g / min, and power of 39-43kW.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The element composition of the high-purity, phase-stable, sintering-resistant zirconia-based coating includes, by mass percentage, Zr: 55-65%, Y: 3.47-6%, Hf: 1.4-1.6%, Si: 0-0.10%, Fe: 0-0.15%, Ti: 0-0.05%, Al: 0-0.10%, O: 30-35%; Preferably, Zr: 55-65%, Y: 4-6%, Hf: 1.4-1.6%, Si: 0-0.10%, Fe: 0-0.15%, Ti: 0-0.05%, Al: 0-0.10%, O: 30-35%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The phase composition of the high-purity, phase-stable, sintering-resistant zirconia-based coating includes t' phase, t phase and c phase, and no m phase; preferably, the volume percentage of t' phase is 60-65%, the volume percentage of c phase is 10-15%, and the rest is t phase.

7. The preparation method according to any one of claims 1 to 6, characterized in that: After the high-purity, phase-stable, sintering-resistant zirconia-based coating is heat-treated for 0-300h@1400℃: the volume percentage of the t′ phase in the coating is not less than 20%, the volume percentage of the m phase is less than 5%, and the rest is the t phase and the c phase; the average grain size is less than 2μm, preferably 1.50-1.60μm.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The grain size of the high-purity, phase-stable, sintering-resistant zirconia-based coating is calculated by the Scherrer formula to be 0.08±0.01 μm, which is in the submicron state; The high-purity, phase-stable, sintering-resistant zirconia-based coating has a grain growth activation energy of 223.05±14.96 kJ / mol.

9. A high-purity, phase-stable, sintering-resistant zirconia-based coating obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Cited By

  • Low-thermal-conductivity anti-sintering thermal barrier coating material as well as preparation method and application thereof

    CN119707488A